2001
DOI: 10.1038/sj.ejcn.1601144
|View full text |Cite
|
Sign up to set email alerts
|

Food and nutritional profile of high energy density consumers in an adult Mediterranean population

Abstract: Objective: To test if an adult Mediterranean population consumes different food volumes while spontaneously ingesting diets of different energy density and to estimate which are the food and nutritional pro®les of these diets. Design: A cross-sectional study of food consumption. Setting: Faculty of Medicine and Health Sciences, Universitat Rovira i Virgili, Reus. Subjects: Five hundred and seventy two adult individuals (25 ± 65 y) randomly selected from the population census of Reus. Intervention: 24 hour reca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 19 publications
4
40
1
4
Order By: Relevance
“…Some of them found a positive relationship between ED and weight (10,14,15,19) , whereas some others found no significant association (13,20) or only in men (16) . Among the few longitudinal analysis available in free-living subjects, two were performed in women only (21,22) and one in both sexes (23) .…”
Section: Body Fat Distribution: Cohort Studies: Diet Quality: Energy mentioning
confidence: 97%
See 1 more Smart Citation
“…Some of them found a positive relationship between ED and weight (10,14,15,19) , whereas some others found no significant association (13,20) or only in men (16) . Among the few longitudinal analysis available in free-living subjects, two were performed in women only (21,22) and one in both sexes (23) .…”
Section: Body Fat Distribution: Cohort Studies: Diet Quality: Energy mentioning
confidence: 97%
“…Some studies have reported positive associations between ED and EI (4,10,11) . In addition, there is a strong correlation between the ED of foods and their fat content (4,12) , which may also encourage weight gain.However, the results from cross-sectional epidemiological studies that have examined the relationships between dietary ED and body-weight status are not consistent (10,13 -20) .Some of them found a positive relationship between ED and weight (10,14,15,19) , whereas some others found no significant association (13,20) or only in men (16) . Among the few longitudinal analysis available in free-living subjects, two were performed in women only (21,22) and one in both sexes (23) .…”
mentioning
confidence: 99%
“…Observational studies generally found a direct association between energy intake and energy density (Marti-Henneberg et al, 1999;Cox and Mela, 2000;Stubbs et al, 2000;Stookey, 2001;Darmon et al, 2004). All these studies mainly focused on the association between energy density with energy and macronutrient intake and in some cases, additionally, with body mass index (BMI) (Marti-Henneberg et al, 1999;Cox and Mela, 2000;Stubbs et al, 2000;Cuco et al, 2001;Stookey, 2001;Darmon et al, 2004;Ledikwe et al, 2006b). Recently published data from two large-scale epidemiological studies indicate that high-energy density diets were a risk factor for higher BMI (Kant and Graubard, 2005;Howarth et al, 2006;Ledikwe et al, 2006a;Mendoza et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Because ingestion of most nutrients increases with increasing energy consumption, and energy density increases with energy intake, low-energy density diets, theoretically, are more prone to nutrient inadequacy than are high-energy density diets. On the other hand, evidence indicates the high diet quality of low-energy density diets (Cuco et al, 2001;Kant and Graubard, 2005;Ledikwe et al, 2006b). More studies addressing the question of energy density and diet quality are needed at population scale.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on the effects of ED on intake was conducted under controlled laboratory conditions; relatively few studies characterized the ED of the self-selected diets of adults [12][13][14][15]17 or children 14,16 consuming meals ad libitum in the free-living environment. Two prior crosssectional studies characterized changes in self-selected dietary ED across the lifespan.…”
Section: Introductionmentioning
confidence: 99%